Indirect effects of long-term care insurance: does it affect the hospital expenditures of ineligible disabled individuals - Yi, Yanling; Xin, Jing; Liu, Junxia (Frontiers in Public Health, 2025)
IntroductionThe literature on the impacts of long-term care insurance (LTCI) on medical expenses has primarily focused on beneficiaries or all older adults, leaving theoretical analysis and the effects of LTCI on the ineligible group unexplored. This study investigates the indirect effects of LTCI on the hospital expenditures of disabled individuals who are ineligible for benefits in China.MethodsBased on Becker’s household production function, we construct a theoretical model to analyze the impacts of LTCI on the hospital expenditures of disabled individuals, both eligible and ineligible. Furthermore, we leverage a quasi-experimental design focusing on the regional variation in the rollout of LTCI in the first round of national pilot cities and employ a difference-in-difference (DID) approach to identify the causal effects of LTCI on the hospital expenditures of ineligible disabled individuals, using the unbalanced panel data combined with four waves’ survey data of China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2013, 2015, and 2018 and the corresponding years’ statistical data of China Urban Statistical Yearbook.ResultsTheoretically, we find that LTCI will affect the hospital expenditures of ineligible disabled individuals through a negative substitution effect, a positive output effect, and a negative health effect, just as the effects observed in their eligible counterparts, leading to an ambiguous total effect. Empirically, we demonstrate that the implementation of LTCI in the first round of national pilot cities has reduced the number of hospitalizations, the total inpatient expenditure, and the out-of-pocket (OOP) inpatient expenditure among ineligible disabled individuals. The effects of LTCI on the hospital expenditures of ineligible disabled individuals are larger among middle-aged or urban groups, and are concentrated in schemes with coverage only of urban employee basic medical insurance, larger beneficiary population, higher reimbursement ceilings, and benefits only in kind. All three mechanisms, including output effect, health effect, and the substitution effect of formal care, are verified, while the substitution effect of informal care remains unclear.ConclusionThis study provides both theoretical and empirical evidence for the stepwise expansion and nationwide coverage of LTCI in China. The findings may also have policy implications for the establishment and development of long-term care (LTC) systems in other middle-income and developing countries confronted with increasing demand for LTC.